x^3+4x^2-7x-28
=x^3-7x+4x^2-28
=x(x^2-7)+4(x^2-7)
=(x+4)(x^2-7)
=(x=4)(x-sqrt7)(x+sqrt7)
2007-07-18 03:59:28
·
answer #1
·
answered by Div 2
·
0⤊
0⤋
x^3+4x^2-7x-28
= (x^3+4x^2) - (7x + 28)
= x^2(x+4) - 7(x+4)
=(x^2 - 7)(x+4)
2007-07-18 10:58:19
·
answer #2
·
answered by olens 2
·
0⤊
0⤋
factor by grouping
(x^3 + 4x^2) - (7x + 28) find GCF of each individual group
x^2 (x+4) - 7 (x+4) and GCF between groups (x+4)
(x+4) (x^2 - 7)
2007-07-18 10:57:49
·
answer #3
·
answered by gfulton57 4
·
0⤊
0⤋
pair your terms 1st 2 terms is x^2(x+4)
2nd pair factors to -7(x+4)
now factor (x+4) to get
(x+4)(x^2-7)
if the 7 were a 9 or 4 or any other square of a number then the difference of squares would be your next factoring move.
2007-07-18 10:59:19
·
answer #4
·
answered by 037 G 6
·
0⤊
0⤋
x^3+4x^2-7x-28
=x^2(x+4) -7(x+4)
=(x^2-7)(x+4)
x= sqrt(7)
or
x= -sqrt(7)
or
x= -4
2007-07-18 10:57:13
·
answer #5
·
answered by fofo m 3
·
0⤊
1⤋
i already answered this for you
(x^2 - 7)(x + 4)
2007-07-18 10:55:18
·
answer #6
·
answered by miggitymaggz 5
·
0⤊
0⤋